ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA RESTORAN BENTOMIE SAMASTA TELAGA KAHURIPANKABUPATEN BOGOR - Utomo, Styo Budi; Karlina, Siti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to find out and analyze how the leadership style is applied at the Bentomie Samasta Telaga Kahuripan Restaurant, Bogor Regency, as well as how this leadership style can influence improving the performance of Bentomie Samasta Telaga Kahuripan Restaurant employees, Bogor Regency. According to Miles and Huberman